Digital Storytelling with Cultural Integrity: How Ritual-Contextual Framing Drives Consumer Trust and Premium Pricing in Balinese Heritage SMEs - Ida Ayu Komang Juniasih; Sagung Agung Diah Pradnya Handayani; I Gusti Gde Oka Pradnyana (Forum Manajemen, 2025)
Balinese small and medium enterprises (SMEs) increasingly rely on social media to reach global tourists, yet face a persistent tension between cultural authenticity and algorithmic marketability. Grounded in semiotic theory and decolonial marketing perspectives, this study examines how heritage-based SMEs navigate this paradox through culturally grounded digital storytelling. Using an explanatory sequential mixed-methods design, we surveyed 190 SME owners across handicraft, homestay, and culinary sectors and conducted 22 in-depth interviews in Ubud, Gianyar, and Badung. Multiple regression analysis indicates that cultural integrity in storytelling significantly predicts consumer trust (beta = .44, p < .001) and willingness to pay premium prices (beta = .31, p = .002), explaining 48% and 33% of variance, respectively. SMEs employing ritual-contextual framing achieved 38% higher engagement and stronger perceived authenticity than those using aesthetic or promotional content. Thematic analysis identifies three narrative mechanisms: ceremonial anchoring, artisan lineage emphasis, and community benefit disclosure. The Culturally Integrity-Driven Digital Storytelling (CIDDS) framework demonstrates that authenticity is strategically performed through indigenous semiotics rather than diluted for platform virality. This study extends decolonial digital marketing theory and provides actionable guidance for heritage SMEs operating in tourism-dependent economies.